Diversity and distribution of viper snakes (Viperidae) in Yogyakarta - Donan Satria Yudha; Afif Fatah Rizki; Firman Arbi; Saliyo Saliyo (Bioma : Berkala Ilmiah Biologi, 2026)
Research on venomous snake’s diversity in Yogyakarta has been conducted. Previous research showed that there were 3 species of viper snakes in Yogyakarta. Viper snakes are highly venomous with hemotoxin venom. Viper’s snakebite cases occurred in Bantul, Kulon Progo and Gunungkidul while antivenom is not yet available in Indonesia. The reseach aim was to determine species and distribution of viper snakes in Yogyakarta. Sampling used were VES, transect and time search methods. Sampling was carried out twice a day. Four species of viper snakes were found in Yogyakarta: Trimeresurus albolabris, Trimeresurus insularis, Craspedocephalus puniceus, and Calloselasma rhodostoma. Shannon-Wiener Diversity Index (H’) in forested hill was 0.264; in forested lowland was 0, and in human settlement in lowland was 0.318. Distribution of vipers in Yogyakarta is uneven, mostly found in forested areas and rivers with riparian vegetation, particularly Trimeresurus albolabris. Craspedocephalus puniceus distribution was on montane forest with cool temperatures. Calloselasma rhodostoma distribution was on submontane karst with quite hot temperatures. These research provide most up-to-date data on viper’s species diversity and distribution. This result can be a reference for ministry of health to produce and evenly distribute specific antivenom especially for vipers, and for health services and hospitals to prepare antivenom when snakebite accident occur.